2016
DOI: 10.1103/physrevb.94.054409
|View full text |Cite
|
Sign up to set email alerts
|

Spin-transfer torques in antiferromagnetic textures: Efficiency and quantification method

Abstract: We formulate a theory of spin-transfer torques in textured antiferromagnets, which covers the small to large limits of the exchange coupling energy relative to the kinetic energy of the intersublattice electron dynamics. Our theory suggests a natural definition of the efficiency of spin-transfer torques in antiferromagnets in terms of welldefined material parameters, revealing that the charge current couples predominantly to the antiferromagnetic order parameter and the sublattice-canting moment in, respective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…Haney et al 90 have shown that an antiferromagnet can also generate a torque on a ferromagnet. Similarly to ferromagnets, a spin-transfer torque is also predicted to occur for an antiferromagnetic domain wall 84,91,92 . All of these investigations, however, considered ballistic transport in perfectly epitaxial and commensurate heterostructures.…”
Section: Box 1 -Antiferromagnetic Spin Valves and Tunneling Junctionsmentioning
confidence: 98%
“…Haney et al 90 have shown that an antiferromagnet can also generate a torque on a ferromagnet. Similarly to ferromagnets, a spin-transfer torque is also predicted to occur for an antiferromagnetic domain wall 84,91,92 . All of these investigations, however, considered ballistic transport in perfectly epitaxial and commensurate heterostructures.…”
Section: Box 1 -Antiferromagnetic Spin Valves and Tunneling Junctionsmentioning
confidence: 98%
“…This conclusion may appear unsatisfactory given that there are a number of theoretical studies reporting the existence of a spin torque in continuous textures inside antiferromagnets 28 . Although the antiferromagnetic orders in the lead and the dynamical antiferromagnetic free-layer individually do not vary in space in our model, the difference in the orientation between the lead and dynamical antiferromagnetic moments can be considered as an extreme limit of spatial texture.…”
Section: (D20)mentioning
confidence: 99%
“…We note that thisẑ form is generic in the case where l denotes the crystalline momentum. 28 Specifically for a checker board structure, t l and l correspond to the Fourier transforms of the nearest-neighbor and next-nearest-neighbor hopping amplitudes respectively. 2∆ ex is the exchange split of the antiferromagnetic electrons.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the spin conservation and the absence of momentum-dependent SOC field, which do not lead to the spin decoherence through the Dyakonov-Perel mechanism 30 during the scattering. The spin current may have interesting interactions with the local magnetic moments 31 , which is worth further study.…”
Section: Model and Candidate Materialsmentioning
confidence: 99%